THE INFLUENCE OF THE RESIDUAL COPPER ON THE PIPES STEEL’S HOT PLASTICITY IN ACCORDANCE WITH REQUIREMENTS - Rusanescu, Carmen Otilia; Rusanescu, Marin (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
Considering the importance of gaseous or liquid fuels impact on the environment, we studied resistance pipelines at hot plastic deformation in order to avoid or reduce any adverse impact on the environment. We studied the influence of residual copper on hot deformability of steel pipes, taking into account that the copper presence in steel, leads to surface defects during the hot deformation. The negative influence of copper, as a residual element of the carbon steel pipes, was proved using torsion deformation at temperatures above 10000C. The experiments was carried, for comparation, both in the air and in the argon atmospheres. Steels plasticity was determined by torsion test using Setaram type machine. The samples was heated and then deformed at different temperatures with a deformation speed constant. For each test, the momentum and number of torsions to fracture were wrote. We studied the structural aspects of materials. The metallographic analysis of the steels which contains copper at the maximum allowed limit for 12500C deformation showed, using SEM, copper presence at the samples surfaces of the Fe lower areas due of the oxidation when heating.Oil transport pipes made ​​by its security features prevent or reduce any resistance detrimental environmental impact.